Long-term effects of in utero and lactational exposure to butyl paraben in female rats - Guerra, Marina Trevizan [UNESP]; Sanabria, Marciana [UNESP]; Cagliarani, Stephannie Vieira [UNESP]; Leite, Gabriel Adan Araújo [UNESP]; Borges, Cibele dos Santos [UNESP]; De Grava Kempinas, Wilma [UNESP] (Wiley, 2017)
Parabens are used as preservatives in cosmetic, pharmaceutical, and food industries, and are frequently detected as contaminants in human fluids and tissues. The endocrine disrupting effects of parabens in female rodents include uterotrophic response, steroidogenesis impairment, and ovarian disturbances. The objective of this study was to determine the effects of maternal butyl paraben (BP) exposure on female sexual development. Pregnant Wistar rats were treated subcutaneously with either corn oil or BP at doses of 10, 100, or 200 mg/kg, from gestational day (GD) 12 until GD 20 for female foetal gonad evaluation, and from GD 12 until the end of lactation to evaluate sexual parameters on the female offspring. Immature female rats were also used in the uterotrophic assay to evaluate the possible estrogenic action of parabens. Our results revealed that, in this experimental protocol, BP did not show estrogenic activity at the doses used and did not impair sexual development and fertility capacity in the female rats, but impaired sexual behavior. We conclude that brain sexual development may be more sensitive to BP effects and we speculate that doses higher than 100 mg/kg (the male lowest observed adverse effect level (LOAEL) for rodent reproductive parameters) would be necessary to promote damages in the female reproduction, regarding the same protocol of exposure. © 2016 Wiley Periodicals, Inc. Environ Toxicol 32: 776–788, 2017.
Keywords: endocrine disrupting chemicals; female reproduction; paraben; uterotrophic assay